Concepts and methods for the study of Chinese religions. - Laliberté, André; Travagnin, Stefania (Religion and Society, 2019)
The three-volume project 'Concepts and Methods for the Study of Chinese Religions' presents a history of the study of Chinese religions. It evaluates the current state of scholarship, discusses a variety of analytical approaches and theories about methodology, epistemology, and the ontology of the field. The three books display an interdisciplinary approach and offer debates that transcend national traditions. It engages with a variety of methodologies for the study of East Asian religions and promotes dialogues with Western and Chinese voices. This volume covers successive historical stages in the study of religion in modern China, draws out the genealogy of major figures and intellectual achievements in a variety of research traditions, and highlights as well the challenges and evolutions experienced by the main disciplines in the last 30 years. This volume serves as a reference for graduate students and scholars interested by religions in modern Chinese societies (i.e., mainland China, Taiwan, Hong Kong and Chinese communities oversea). Using a wide range of methods, from textual analysis to fieldwork, it presents case studies via the disciplines of religious studies, anthropology, sociology, history, and political science